Unraveling Heparan Sulfate Proteoglycan Binding Motif for Cancer Cell Selectivity - Brunetti, Jlenia; Riolo, Giulia; Depau, Lorenzo; Mandarini, Elisabetta; Bernini, Andrea; Karousou, Evgenia; Passi, Alberto; Pini, Alessandro; Bracci, Luisa; Falciani, Chiara (Frontiers in Oncology, 2019)
Membrane HSPGs regulate cell proliferation, migration and differentiation, for these reasons they are considered key players in cancer cells development processes. Here we investigate how the sulfation pattern of HSPG on cells can drive specificity of binding, using NT4 peptide. NT4 is a branched peptide that binds to the GAG chains of HSPGs. Importantly, NT4 already showed to inhibit growth factors-induced migration and invasiveness of cancer cells, implying antagonist binding on HSPG. Binding affinity of NT4 with recombinant HSPGs showed that NT4 bound both glypican-3 and -4, and, with lower affinity, syndecans-4. NT4 binding to the cancer cell membrane inversely correlated with expression of sulfatases. NT4 binding was higher in cell lines with lower expression of SULF-1 and SULF-2, which confirms the determinant role of sulfate groups for recognition by NT4. Using 8-mer and 9-mer HS oligosaccharides with analog disaccharide composition and different sulfation sites, a possible recognition motif was identified that includes repeated 6-O-sulfates, alternated with N- and or 2-O-sulfates. A fully descriptive picture of the binding architecture was given by the molecular modeling showing that sulfate groups lying on opposite sides of the oligosaccharide can interact with positive residues on two peptide sequences of the branched structure, thus favoring multivalent binding, which explains the high affinity and selectivity of NT4 for highly sulfated GAGs. NT4 and possibly newly selected branched peptides will be essential probes to reconstruct and unravel binding sites for cancer-involved ligands on GAGs that will open up for new options for cancer detection and treatment.